A study of magnitude of anemia and its association with diet pattern in young females (Panacea Journal of Medical Sciences, 2020)
Background: Due to lack of consumption of nutrients by cell the Nutritional anemia occurs. Iron, folic acid, Vitamin B12, Vitamin B6, Vitamin C and protein are vital nutrients whose deficiency can lead to nutritional anemia.Aim: To study the magnitude of anaemia in young females and its association with diet pattern.Materials and Methods: Study was done as a cross-sectional study in young females of age 18 to 40. Demographic details like age, height, body weight, and the dietary patterns comprising food habits were recorded. Hematological parameters were obtained using automated haematology cell counter and peripheral blood smears by microscopy.Results: In this study 100 females were included, 62% of participants were anemic, the mean years of age in the study participants was 26.52±3.48 years. 44% of participants had mild anemia followed by 16% had moderate anemia and 2% had severe anemia. On further analysis of dietary habits, 47% of women not taking green leafy vegetables had mild to moderate anemia, 25% of women drinking tea or coffee after the meal had mild anemia and 14% of women eating junk foods and 5% of women eating less fruits had mild to moderate anemia.Conclusion: Improving women’s health education on the consumption of iron-rich foods and healthy diet habits is instrumental in preventing nutritional anemia could be the single most important intervention to reduce India’s anemia burden.